2001
DOI: 10.1111/j.1540-8183.2001.tb00745.x
|View full text |Cite
|
Sign up to set email alerts
|

Patent Foramen Ovale Closure in Patients with Transient Ischemia Attack/Stroke

Abstract: Paradoxical embolism through a patent foramen ovale (PFO) has been recognized as a potential cause of transient ischemia attack (TIA) and stroke especially in younger patients. The therapeutic options are medical treatment (antiaggregation or anticoagulation) with an annual recurrence rate of 3% to 4% for stroke or TIA, surgical PFO closure, or catheter closure. Randomized studies are ongoing; however, the results will not be available soon. Since August 1994, we have attempted catheter closure of a PFO in 281… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
59
0
2

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(63 citation statements)
references
References 56 publications
2
59
0
2
Order By: Relevance
“…Surgery has been superseded by the percutaneous transcatheteral approach due to the absence of open-heart surgery [25]. After early experiences in which the success in the reduction of ischaemic events was balanced by a high rate of periprocedural complications, subsequent studies using multiple device systems have demonstrated similar rates of recurrent thromboembolic events [26][27][28][29][30][31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…Surgery has been superseded by the percutaneous transcatheteral approach due to the absence of open-heart surgery [25]. After early experiences in which the success in the reduction of ischaemic events was balanced by a high rate of periprocedural complications, subsequent studies using multiple device systems have demonstrated similar rates of recurrent thromboembolic events [26][27][28][29][30][31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…Transesophageal echocardiography (TEE) is considered the standard approach to guide those interventions, 6 but supine patients do not tolerate the transesophageal probe well, so that most centers use more or less extensive fluoroscopic imaging when performing device closure, although fluoroscopy cannot sufficiently depict the spatial relation between occluder device and cardiac structures next to the interatrial communication. Rapidly growing clots on the device are not shown either.…”
Section: Introductionmentioning
confidence: 99%
“…Surgical occlusion has been sporadically reported in the literature 38,39 , with recurrence rates similar to those found with clinical treatment (3-5%) However, it has intrinsic disadvantages because it is an invasive procedure with significant morbidity, especially regarding thoracotomy and extracorporeal circulation. With the advent and improvement of devices for occlusion of atrial septal defects, these patients have also been successfully treated in the catheterization laboratory [40][41][42][43][44] . Despite the absence of prospective and randomized studies in the literature, comparing clinical treatment with anticoagulants and percutaneous closure of atrial septal defects, longitudinal studies from series of patients suggest that percutaneous treatment is, at least, as effective as clinical treatment, decreasing the recurrence rate to around 2-4% per year [41][42][43][44][45] .…”
Section: Discussionmentioning
confidence: 99%
“…With the advent and improvement of devices for occlusion of atrial septal defects, these patients have also been successfully treated in the catheterization laboratory [40][41][42][43][44] . Despite the absence of prospective and randomized studies in the literature, comparing clinical treatment with anticoagulants and percutaneous closure of atrial septal defects, longitudinal studies from series of patients suggest that percutaneous treatment is, at least, as effective as clinical treatment, decreasing the recurrence rate to around 2-4% per year [41][42][43][44][45] . Furthermore, taking into account the intention to treat it is probably more effective because it is permanent, since many patients discontinue anticoagulant treatment after some time.…”
Section: Discussionmentioning
confidence: 99%